Eyewitness Mesopotamia - Steele, Philip, 1948- (London ; New York : DK Pub., 2007)
Full-color illustrated photographs describe the history, culture, and people of Ancient Mesopotamia. Includes Mesopotamia clip-art CD-ROM and wall chart.
Land between two rivers -- Sumerian city--states -- Mighty rulers -- Story of writing -- Gods and goddesses -- City life -- Country life -- Death and burial -- Akkad's rise and fall -- Ziggurats and temples -- Games, music, and sports -- Crafts and technology -- Rise of Babylon -- Learning and scholars -- Wider horizons -- Trade and commerce -- Transportation and travel -- Assyrian Eempire -- Ancient warfare -- Art of hunting -- Assyrian palaces -- Epic of Gilgamesh -- Assyrian knowledge -- Babylon reborn -- At the center of the world -- Persians -- Classical age -- Islamic age -- Uncovering the past -- Timeline of Mesopotamia -- A to Z of famous people -- A to Z of ancient sites -- Glossary -- Index.
Includes index.
Includes bibliographical references (pages 69) and index.
Keywords: Mesopotamia -- Juvenile literature; Ancient civilizations -- Middle East -- History -- Juvenile literature; Iraq -- Civilization -- To 634 -- Juvenile literature